Cortico-muscular and cortico-cortical coherence changes resulting from Perampanel treatment in patients with cortical myoclonus. Issue 5 (May 2021) - Franceschetti, S.; Visani, E.; Rossi Sebastiano, D.; Duran, D.; Granata, T.; Solazzi, R.; Varotto, G.; Canafoglia, L.; Panzica, F.
Highlights: In patients with progressive myoclonus epilepsy, cortico-muscular coherence significantly decreased during Perampanel treatment. Out-degree and betweenness centrality increased on contralateral motor cortex during Perampanel treatment. The improvement of the myoclonus induced by Perampanel resulted from restored leadership of the contralateral motor cortex. Abstract: Objective: To investigate the mechanisms by which Perampanel (PER) reduces the severity of action myoclonus, we studied on MEG signals the changes occurring in cortico-muscular coherence (CMC) and cortico-cortical connectivity in patients with progressive myoclonus epilepsies. Methods: The subjects performed an isometric extension of the hand; CMC and cortico-cortical connectivity were assessed using autoregressive models and generalized partial-directed coherence. The contralateral (Co) sensors showing average CMC values >0.7 of the maximum (set to 1) were grouped as central (C) regions of interest (ROI), while adjacent sensors showing CMC values >0.3 were grouped as Surrounding (Sr) ROIs. Results: Under PER treatment, CMC decreased on Co C and Sr ROIs, but also on homologous ipsilateral (Ip) ROIs; out-degrees and betweenness centrality increased in Co ROIs and decreased in Ip ROIs. The flow from Ip to Co ROIs and from activated muscles to Ip C ROI decreased. Conclusion: The improvement of myoclonus corresponded to decreased CMC and recovered leadership of the cortical regions directly involved in the motor task, with a reduced interference of ipsilateral areas. Significance: Our study highlights on mechanisms suitable to treating myoclonus and suggests the role of a reduced local synchronization together a better control of distant synaptic effects.